Соціальна безпека в системі соціологічного знання - Тімощук, Марина Сергіївна; Тимощук, Марина Сергеевна; Timoshchuk, Maryna S. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Здійснення теоретичного аналізу соціальної безпеки, із погляду різних наукових підходів, актуалізується вивченням соціальної безпеки як важливого інструменту щодо забезпечення життєдіяльності суспільства. До вивчення соціальної безпеки застосовано системний метод. З’ясовано сутність системи соціальної безпеки, у якій людина, суспільство й держава виступають одночасно її суб’єктом та об’єктом. Окреслено потребу у виокремленні «генералізуючого» виду безпеки для детального вивчення явищ соціальної безпеки. Implementation of the theoretical analysis of social security in terms of different scientific approaches is actualized through the study of social security as an important tool ensuring the life of society. In particular, the security issue is studied in the works of the most prominent sociologists (O. Kont, H. Spencer, E. Durkheim, M. Weber, R. Merton), and theorists of postindustrial society (U. Beck, K. Popper). The systemic method is applied to the study of social security. The essence of the social security system is clarified, in which an individual, society and the government serve both as its subject and object. The need for distinguishing the «generalizing» type of safety for a detailed study of the phenomena of social security has been outlined. The concept of social security subsystem as an independent system that stands as a set of social interactions of an individual, society and the government has been studied as well.
Social Security in the System of Sociological Knowledge
Keywords: безпека; соціальна безпека; суспільство; держава; система; security; social security; society; government / state; system